PENGARUH REMUNERASI DAN KERJASAMA TIM TERHADAP KINERJA YANG DIMEDIASI KEPUASAN KERJA PADA ANGGOTA POLISI SATUAN LALU LINTAS POLRES KENDARI - Lesmana Pramuditya Primajati; Dedy Takdir Syaifuddin; La Ode Bahana Adam (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2023)
This study aims to analyze and explain the effect of remuneration and teamwork on performance mediated by job satisfaction for members of the Kendari Police Traffic Unit. This research approach is a survey with an explanatory research design. Data collection was carried out in a cross-sectional manner using an instrument in the form of a questionnaire. The population of this study were 64 members of the Kendari Police Traffic Unit. The analytical method used for testing the hypothesis of this study is Partial least square (PLS). The results showed that remuneration and teamwork had a positive and significant effect on job satisfaction and police performance. Then job satisfaction has a positive and significant effect on police performance. Furthermore, job satisfaction acts as a partial mediation on the effect of remuneration and teamwork on police performance. This means that the increase in job satisfaction is significantly influenced by remuneration and teamwork. Furthermore, job satisfaction has a significant contribution to improving police performance. Thus, good remuneration and teamwork contribute significantly to improving police performance directly or indirectly through mediating job satisfaction